Rhodococcus equi e metabolismo do ferro: associação com susceptibilidade genética e sobrevivência em macrófagos - Gressler, Letícia Trevisan (2016)
Horse breeding industry is an activity in ascension worldwide, and is responsible for generating jobs and income. In Brazil, especially in Rio Grande do Sul state, there are several horse breeding farms with high-standard equines. Although these herds are under strict sanitary control, the occurrence of respiratory diseases is an important cause of mortality in foals and reduced athletic performance. Among the respiratory diseases, equine rhodococcosis, caused by the bacterium Rhodococcus equi, is the major cause of pneumonia in foals. Rhodococcus equi is worldwide distributed, and have emerged as an important cause of economic losses due to pneumonia in young animals. However, preventive measures and effective control of the disease are still challenges to be reached. In R. equi infection, iron (Fe) is classified as an essential element not only for the bacterium multiplication, but also as a key for the expression of virulence factors. Studies have shown the presence of specific Fe uptake mechanisms in R. equi, which have been determining its survival in both saprophytic and pathogenic life styles. However, as a type of nutritional immunity, mammals, including horses, reduce the plasmatic concentration of Fe through its binding in proteins, including the transferrin (Tf). In this context, the present thesis was developed to study aspects related to metabolism and acquisition of Fe by R. equi and Fe importance in the pathogenesis of equine rhodococcosis (manuscript 1), control and treatment of infections caused by R. equi through drugs with capability to reduce the availability of intracellular Fe (manuscript 2), and genetic susceptibility to R. equi pneumonia (manuscript 3), including the assessment of polymorphisms in the equine Tf gene as risk factors related to susceptibility and/or resistance to equine rhodococcosis (manuscript 4 ). We conclude that R. equi is evolving to specialize it in the acquisition and utilization of Fe from the host, skills that should be considered as key points for the development of chemotherapeutic agents. Once R. equi encodes redundant mechanisms of acquisition and utilization of Fe, it is likely that chemotherapeutic agents will need act on multiple cellular mechanisms or be used in combination. Furthermore, the term "nutritional immunity" may be considered an important strategy to minimize antimicrobial resistance observed in R. equi. As an example of chemotherapy associated with iron metabolism, we observed that chloroquine inhibits the intracellular multiplication of R. equi, most likely due to intracellular iron deprivation. However, further studies are necessary to evaluate the chloroquine therapeutic potential against R. equi infections. We also observed important chromosomal regions positively associated with R. equi pneumonia, which seem to possess genes associated with immune response against intracellular pathogens. This observation allows us to classify the equine rhodococcosis as a disease of polygenic basis, as postulated by previous studies. Finally, we found that polymorphisms in the Tf gene, including some not described yet in the literature, occur in Brazilian Sport Horses and Brazilian Thoroughbred Horses. There is the occurrence of two alleles between the breeds studied, including heterozygosis for these alleles. We believe that there is a relationship between equine Tf variants, and genetic susceptibility to R. equi pneumonia in the breeds evaluated. Summarizing, we have demonstrated that the modulation of Fe availability may be a useful approach to control the disease.